Progression and effect of cognitive-behavioral changes in patients with amyotrophic lateral sclerosis. Issue 6 (December 2017) - Bock, Meredith; Duong, Y.-Nhy; Kim, Anthony; Allen, Isabel; Murphy, Jennifer; Lomen-Hoerth, Catherine
Abstract: Background: To prospectively evaluate the progression of cognitive-behavioral function in amyotrophic lateral sclerosis (ALS) and examine the association of cognitive-behavioral deficits with disease progression, patient quality of life (QOL), and caregiver burden. Methods: We evaluated cognitive-behavioral function using the Amyotrophic Lateral Sclerosis Cognitive Behavioral Screen at enrollment and after 7 months in a cohort of patients with ALS. Paired t tests were used to evaluate the change in the 2 assessments. Linear regression and Kruskal-Wallis tests were applied to investigate how initial cognitive or behavioral status related to outcomes. Results: The mean test-retest interval was 6.8 months (SD 1.6). Cognitive status of the study population (n = 49) overall did not change over the study period ( p = 0.06) despite progression of motor weakness ( p < 0.001), though small subsets of the sample demonstrate cognitive change. Patients initially classified as behaviorally normal showed increased behavioral problems over time ( t = −2.8, p = 0.009). Decline in cognitive (β = −1.3, p = 0.03) and behavioral (β = −0.76, p = 0.002) status predicted increasing caregiver burden. Behavioral abnormalities predicted decline in forced vital capacity and ALS Functional Rating Scale–Revised score ( p = 0.008, 0.012) in the study population and patient QOL in the most severely affected group ( t = 4.3, p = 0.003). Conclusions: Cognitive-behavioral change is a key aspect of disease heterogeneity in ALS. Executive function in ALS overall remains stable over 7 months as detected by an administered screening tool. However, patients may develop caregiver-reported behavioral symptoms in that time period. Screening for caregiver-reported symptoms has a particular utility in predicting future clinical decline, increased caregiver burden, and worsening patient QOL.